The physical and psychosocial problems of the patients young adults with moderate leukemia) Al-Shadid) in Baghdad (Journal of the College of Basic Education, 2022)
Objectives: To know: 1- The physical and psychosocial problems of young patients with anemia.Intermediate (extreme) whiteness. 2- The relationship between physical problems and age. 3- The relationship between psychosocial problems and the patient's profession.4- The relationship between psycho-social problems and physical problems. Study methodology